Impact of Authentic Leadership on Organizational Citizenship Behavior by Using The Mediating Effect of Psychological Ownership - Erum Shaikh; Waqas Ahmed Watto; Muhammad Nawaz Tunio (Faculty of Economic and Business, 2022)
The study objective was to examine the role of psychological ownership as a mediator concerning organizational citizenship behavior and authentic leadership. A structured questionnaire was selected to gather primary data from 300 respondents of the telecom sector of Lahore; 263 questionnaires were selected valid. This research use employees of four different companies in the telecom sector as samples. This research uses correlation, independent sample t-test, and one-way ANOVA. The empirical result shows that authentic leadership positively relates to organizational citizenship behavior. According to the findings of this study, psychological ownership partially mediates the relationship between organizational citizenship behavior and authentic leadership among the employees of the telecommunication sector of Pakistan. The Implication of this study is limited to the telecom sector of Pakistan. How to Cite:Shaikh, E., Watto, W. A., & Tunio, M. N. (2022). Impact of Authentic Leadership on Organizational Citizenship Behavior by Using The Mediating Effect on Psychological Ownership. Etikonomi, 21(1), 89-102. https://doi.org/10.15408/etk.v21i1.18968.